Performance and health effects of Zuprevo 18% in newly received, highly stressed beef cattle - Ethan R. Schlegel; Dale A. Blasi; William R. Hollenbeck; Brandon E. Oleen; David G. Renter; Mark F. Spire (Kansas Agricultural Experiment Station Research Reports, 2014)
The objective of this study was to determine the health and performance effects of Zuprevo 18% (tildipirosin, 4 mg/kg body weight) during a 42-day backgrounding period when administered to high-risk transported cattle within 24 hours after arrival.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Bovine respiratory disease; Zuprevo; Calves